The realize of the farm field information spatial analysis based on palm-sized PC - FANG Hui; SHAO Yong-hua; HE Yong (浙江大学学报. 农业与生命科学版)
Variance process is the key of precision farming. The first step of variance process is sampling and the next is analysis of the data acquired. To analyze data on-line, the spatial analysis model based on Palm-sized PC was developed. This model constitutes part of a farm field information collection system. So the system can not only take sampls in time but also analyze the acquired data immediately. And the visualization technology is also used to show the analysis result directly and instantly.